Enhancing Managerial Skills for MSME Practitioners Through Community-Based Education Programs - Suhartono, Edy; Adianita, Happy; Handayati, Ratna; Nurcholidah, Lilik; Sulaeman, Moh. Muklis (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
MSMEs play a crucial role in driving the economy, both locally and nationally. Many MSMEs face challenges in managing their businesses, especially in terms of management. This research aims to examine strategies for enhancing managerial skills for MSME practitioners through community-based education programs. This research methodology employs a qualitative approach with a focus on community engagement, combined with a literature review. Descriptive analysis is used to analyze data obtained from 27 selected articles taken from Google Scholar within the range of 2008-2024. The study findings indicate that in an era of globalization fraught with challenges, the development of managerial skills becomes paramount for Micro, Small, and Medium Enterprises (MSMEs) practitioners. Despite their vital role in a country's economy, MSMEs often encounter difficulties in effectively managing their businesses due to insufficient knowledge and managerial skills. In this context, strategies for enhancing managerial skills through community-based education programs offer relevant and affordable solutions.